Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The problem is:

Let G and G' be groups, and let H and H' be normal subgroups of G and G', respectively. Let $\phi$ be a homomorphism of G into G'. Show that $\phi$ induces a natural homomorphism

$$\phi_*: (G/H) \rightarrow (G'/H)\ \text{if}\ \phi[H] \subseteq H'.$$ (This fact is constantly used in algebraic topology.)

Attempt at a solution:

$\phi: G \rightarrow G'$

$\phi_*(gH) = \phi(g)H'$ where $gH$ is the class of $g$ in $\frac{G}{H}$ and $\phi(g)H'$ is the class of $\phi(g)$ in $\frac{G'}{H'}$.

$$\phi_*((aH)(bH)) = \phi_*((ab)H)$$

$$ = \phi(ab)H'$$

$$= \phi(a)\phi(b)H'$$

$$= \phi(a)H'\phi(b)H'$$

$$=\phi_*(aH)\phi_*(bH)$$

share|cite|improve this question
up vote 1 down vote accepted

Ok, but you have to verify that $\phi_*$ is well-defined. In order not to repeat the same computations all the time, remember the homomorphism theorem:

If $H$ is a normal subgroup of $G$, there is a surjective homomorphism $p : G \to G/H$ with kernel $H$. If $K$ is a group, then every group homomorphism $f : G \to K$ which vanishes on $H$ has a unique extension to a homomorphism $\overline{f} : G/H \to K$, i.e. $\overline{f} \circ p = f$.

Here, you can use the composition $f : G \stackrel{\phi}{\to} G' \to G'/H'$. The assumption $\phi(H) \subseteq H'$ means exactly that $f$ vanishes on $H$. Thus, it extends to a homomorphism $G/H \to G'/H'$. No computation is needed at all. In general, it is good to forget about cosets at all and just remember the universal property of $p : G \to G/H$ above.

share|cite|improve this answer

Looks fine, but you missed to check well-definedness ... that is: If $g, g' \in G$ have the same coset modulo $H$, $gH = g'H$, then the image of this coset has to be unabiguously defined, so we must have $\phi_*(gH) = \phi_*(g'H)$, meaning $\phi(g)H' = \phi(g')H'$ for $g,g' \in G$ with $gH = g'H$.

share|cite|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.